Pengaruh Akupresur Titik SP6 dan LI4 terhadap Pengurangan Intensitas Nyeri Kala I Persalinan di PMB NY. T.O Desa Klapanunggal Kabupaten Bogor - Imelda Diana Marsilia; Sri Kubilawati (Jurnal Akademika Baiturrahim Jambi, 2022)
Labor pain can cause stress which causes excessive release of hormones such as catecholamines and steroids. Pain in the active phase is physiological pain that occurs for a longer time, for that we need an effort to deal with pain in the first stage of labor. If pain in labor is not overcome, it will cause problems that are not only painful for the mother in labor, but also have the potential to threaten the life of the fetus. One technique that can be done to reduce the intensity of labor pain is to provide acupressure techniques. This study aims to determine the effect of acupressure points SP6 and L14 on reducing pain intensity in the first stage of labor at BPM Ny. T.O Klapanunggal Village, Bogor Regency. This research is a Quasi Experimental Design using the One Group Pre-Post Test Design approach. The population in this study were all maternity mothers who had their pregnancy checked at BPM Ny. T.O. The sampling technique was carried out by accidental sampling and obtained a sample of 25 respondents. The study was conducted from July to August 2021. The data was collected by observing the acupressure treatment with the Numerical Rating Scale (NRS). Univariate analysis using frequency distribution and Bivariate analysis using paired t-test. The results of the study that the average labor pain before being given the SP6 and L14 acupressure techniques was 6.48 and after being given the SP6 and L14 acupressure techniques was 3.84. There is an effect of SP6 and L14 acupressure techniques on labor pain in the first stage of active phase at BPM Ny. T.O (p–value 0.0001 < 0.05) with a decrease of 2.64. Acupressure therapy can be applied to midwifery care for mothers in the first stage of labor, which aims to reduce labor pain.